Do corpo ameaçado ao corpo como ameaça: discursos sobre o alcoolismo na Fortaleza das primeiras décadas do século XX - Sales, Thiago Gomes (2022)
The present study aims to investigate how the consumption of alcoholic beverages became a social problem in the city of Fortaleza during the first decades of the 20th century. In addition to that, one of the objectives is also to discuss how the semantic operation that classified the custom of drinking “cachaça” as an unnatural behavior — therefore a subject to repress — became viable. The consulted documentation, composed of medical journals, journalistic articles, criminal proceedings and literary reports, led the investigation to three discursive devices that contributed, each in its own way, to enable the institution of scientific medical knowledge about the numb body. The first and second devices, associated with the concepts of race and evolution, respectively, made it possible to frame the habit of drinking alcoholic beverages as a source of biological degeneration and, therefore, as a risk to the community, which, in turn, made it possible to change, the condemnation of a habitual drunk to longer terms of imprisonment. Less complex than the first two, the third device was constituted with the aim of removing the subject from the numb body while instituting the narcotic substance itself as a subject of the possessed body. Such displacement was intended to make possible the classification of the numb body as a body without a subject, without control, or, what is worse, as a body controlled by the physical and chemical processes triggered by the substance, which would make the medical initiative legitimate to undertake the resumption of this sick body by the practices of progress, since the taking of power over a body that is no longer aware of itself, emptied of reason, will be socially understood as legitimate and altruistic.